Sarcastic Expressions in Two American Movies - Emhasib Sandi Bachtiar; Tofan Dwi Hardjanto (Lexicon, 2018)
This study investigates the sarcastic utterances found in two American movies. The data for the research were dialogues containing sarcastic expressions found in the movies Fantastic Four (2005) and its sequel Fantastic Four: Rise of the Silver Surfer (2008). The data were analyzed and categorized according to their forms using Camp’s theory (2011). The sarcastic utterances were also classified according to their functions using Leech’s theory (1983). The results indicate that in terms of form, illocutionary sarcasm (60%) was most frequently used by the characters in the movies, which suggests that the characters in the movies tend to express their sarcasm through illocutions. In terms of function, sarcasm in the movies was more commonly (56%) used for collaborative purposes. The results of the research also suggest that there has to be a clear context in understanding sarcastic expressions, and the interlocutors must share some sufficient common ground in employing sarcasm.